Solvothermal Synthesis of Zn2SnO4 Nanocrystals and Their Photocatalytic Properties - Guang Sun; Saisai Zhang; Yanwei Li (International Journal of Photoenergy)
Crystalline Zn2SnO4 nanoparticles were successfully synthesized via a simple solvothermal route by using Zn(CH3COO)2·2H2O and SnCl4·5H2O as source materials, NaOH as mineralizing agent, and water and ethanol as mixed solvents. The used amount of NaOH was found to have an important influence on the formation of Zn2SnO4. When the molar ratio of OH− : Zn2+ : Sn4+ was set in the range from 4 : 2 : 1 to 8 : 2 : 1, Zn2SnO4 nanoparticles with different shape and size were obtained. However, when the molar ratio of OH− : Zn2+ : Sn4+ was set as 10 : 2 : 1, a mixture phase of ZnO and ZnSn(OH)6 instead of Zn2SnO4 was obtained. Photodegradation measurements indicated that the Zn2SnO4 nanoparticles own better photocatalytic property to depredate methyl orange than the Zn2SnO4 nanopolyhedrons. The superior photocatalytic properties of Zn2SnO4 nanoparticles may be contributed to their small crystal size and high surface area.